Merawat Toleransi Di Desa Palongaan Sebagai Desa Umat Rukun Beragama - Frans Fandy Palinoan; Petrus Bine Saramae; Estepani Piska (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The diversity of religions in Polongaan Village is the uniqueness of the village. Tolerance between religious communities in Polongaan Village is expressed by the way of life of the people who are not exclusive with their differences. The most obvious tolerance of religious communities in Polongaan Village is the arrangement of houses of worship in one complex, so that this village is used as a model for religious harmony. The research method used in this study is a qualitative method by conducting interviews. The results of the study show that the Catholic people in Polongan Village have implemented their faith through concrete actions in the form of tolerance for all religious communities in Polongaan Village.